Biometric recognition : 13th Chinese Conference, CCBR 2018, Urumqi, China, August 11-12, 2018, Proceedings /: 13th Chinese Conference, CCBR 2018, Urumqi, China, August 11-12, 2018, Proceedings. (2018) - Unknown
No abstract available